GC-MS analysis and evaluation of in vitro antioxidant potential and total phenolics content of wild hops (Flemingia strobilifera (L.) W.T. Aiton) - Pizon, J.R.L.; Nuneza, O.M.; Uy, M.M.; Senarath, W.T.P.S.K. (International Journal of Biosciences (IJB), 2016)
Attached
Keywords: Fabaceae; Gas chromatography; Leaf extracts; Scavenging activity.